The features of graphic design clothes expression under production automation - Povchyk, S. (Theory and practice of design, 2016)
The changes in graphic process of designing clothes associated with automation are analyzed. An analysis of recent studies of various aspects of clothing design, introduction of CAD and computer imaging design process. The actuality of investigation forms and methods of use CAD visualization process designing clothes are substantiated. The CAD graphics capabilities at different stages of the project process are examined. The influence of automation technology for the production of clothing design of modern designer is proved. The advantages of innovative visualization design clothes are revealed. The necessity of changes in modern professional training related to changes in operating conditions of sewing production. The arguments according to the importance of solving this problem for the expansion project of space and range of professional responsibilities of modern designers are given.